Traumatic brain injury and post-acute decline: what role does environmental enrichment play? A scoping review - Frasca, Diana; Tomaszczyk, Jennifer; McFadyen, Bradford J.; Green, Robin E. (Frontiers in Human Neuroscience, 2013)
Objectives. While a number of studies provide evidence of neural and cognitive decline in traumatic brain injury (TBI) survivors during the post-acute stages of injury, there is a dearth of research on the possible mechanisms underlying this decline. The purposes of this paper, therefore, are to (1) examine evidence that environmental enrichment (EE) can influence long-term outcome following TBI, and (2) examine the nature of post-acute environments, whether they vary in degree of EE, and what impact these variations have on outcomes. Methods. We conducted a scoping review to identify studies on EE in animals and humans, and post-discharge experiences that relate to barriers to recovery. Results. Ninety-six articles that met inclusion criteria demonstrated the benefits of EE on brain and behaviour in healthy and brain-injured animals and humans. Nineteen papers on post-discharge experiences provided evidence that variables such as insurance coverage, financial and social support, home therapy, and transition from hospital to home, also play a vital role in regaining independence. Conclusion. There is evidence to suggest that lack of EE, whether from lack of resources or limited ability to engage in such environments, may play a role in post-recovery cognitive and neural decline. Maximizing EE in the post-acute stages of TBI may improve long-term outcomes for the individual, their family and society.